2005
DOI: 10.1037/0022-3514.88.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Implicit Power Motivation on Men's and Women's Implicit Learning and Testosterone Changes After Social Victory or Defeat.

Abstract: Two studies examined interactions of implicit power motivation and experimentally varied victory or defeat in a contest on implicit learning of a visuomotor sequence associated with the contest outcome and changes in testosterone and self-reported affect. In men and women, power motivation predicted enhanced learning (sequence-execution accuracy) after a victory and impaired learning after a defeat. In men, power motivation predicted testosterone increases among winners and decreases among losers, and testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
165
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(188 citation statements)
references
References 69 publications
23
165
0
Order By: Relevance
“…Details on this task, which was designed to be strongly rewarding (victory) or frustrating (defeat), are given in Schultheiss et al (2005). Participants in the winning condition "won" all rounds except for the second and the fifth, and participants in the losing condition correspondingly "lost" all rounds except for the second and the fifth.…”
Section: Methodsmentioning
confidence: 99%
“…Details on this task, which was designed to be strongly rewarding (victory) or frustrating (defeat), are given in Schultheiss et al (2005). Participants in the winning condition "won" all rounds except for the second and the fifth, and participants in the losing condition correspondingly "lost" all rounds except for the second and the fifth.…”
Section: Methodsmentioning
confidence: 99%
“…However, as noted by O'Carroll (O'Carroll 1998), the interpretation of these results is complicated by the interesting, and better established, observation that men's testosterone levels also fall in response to failures in dominance contests of various kinds (Archer 2006, Dabbs & Dabbs 2000, Elias 1981, Mazur & Booth 1998, especially for men who strive more for dominance (Schultheiss et al 2005). Archer (2006) proposed that this response is part of a primitive, evolved system by which men's willingness to enter dominance contests is informed by their previous record of success.…”
Section: Some Evidence From Adult Men and Womenmentioning
confidence: 99%
“…More up to date studies showed that the PSE-measured affiliation, power and achievement motives predict affective responses to incentives (e.g., Fodor et al 2006), direct attention (e.g. Schultheiss and Hale 2007), support motive-related goal striving (e.g., Brunstein and Maier 2005), are associated with health outcomes (e.g., Jemmott 1987;McClelland 1979;McClelland et al 1980McClelland et al , 1987 and were shown to have physiological correlates (power: testosterone level, e.g., Schultheiss et al 2005; affiliation: progesterone level, e.g., Schultheiss et al 2003; achievement: release of peptide hormone arginine-vasopression, McClelland 1995). With regard to convergent validity, Spangler's (1992) metaanalysis showed that the TAT and questionnaires were only moderately correlated and predict different kinds of outcome variables.…”
Section: Three Examples Of Implicit Motive Measuresmentioning
confidence: 99%